EFFECT OF ACUPUNCTURE THERAPY AT SHENMEN, NEIGUAN, HEGU, QUCHI POINTS ON CHANGES IN HYPERTENSION AT HOLISTIC NURSING CLINIC PROBOLINGGO - Nurun Ni’mah; Grido Handoko Sriyono; Dodik Hartono (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
A rise in blood pressure above the usual range is referred to as hypertension. Untreated high blood pressure that persists for a long time (persistently) can harm various organs, including the kidneys (kidney failure). Hypertension can be done with pharmacology to non-pharmacological or complementary. The purpose of this study was to determine the effect of acupuncture therapy at Shenmen, Neiguan, Hegu, Quchi points on changes in hypertension at the Holistic Nursing Therapy Clinic in Probolinggo. This type of research uses a pre-experimental research design, with a one-group pre-post test study design. The sample design in this study was 30 patients with high blood pressure using the acidental sampling technique. Instruments used Sinocare BA-801 digital blood pressure gauge. Statistical test using paired T test. The results of the analysis showed that the average blood pressure of respondents before being treated with acupuncture therapy was 158.3/103.0 and the results of the analysis showed that the average blood pressure of respondents after being given acupuncture therapy was 144.6/95.0. From the results of the analysis test, it was found that there was an effect of acupuncture therapy at Shenmen, Neiguan, Hegu, Quchi points on changes in hypertension at the Holistic Nursing Therapy Clinic in Probolinggo with an -value of 0.000. Acupuncture is a therapeutic method by stabbing at points on the body's surface to treat diseases and other health conditions, including hypertension